2000
DOI: 10.2304/ciec.2000.1.2.3
|View full text |Cite
|
Sign up to set email alerts
|

A Child's Say in Parent—Teacher Talk at the Pre-School: Doing Conversation Analytic Research in Early Childhood Settings

Abstract: In this article the authors analyse how one child actively participates in a particular occasion of home-pre-school communication conducted in a pre-school setting. A conversation analytic perspective is adopted to analyse the three-way parent-teacher-child conversation. This instance shows how a child becomes a speaker in the talk rather than being only a topic of talk between adults. The analysis provides an understanding of how the participants collaboratively construct and produce 'the competent pre-school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…The present study mainly draws upon this small, but growing body of literature (e.g. Baker & Keogh 1995Leiminer & Baker 2000;MacLure & Walker 1999Silverman et al 1998). One of the main reasons for the paucity of descriptive research on the subject is the confidential and sensitive nature of PTMs (as underlined in Section 3.1).…”
Section: The Uncharted Territory Of Mediated Ptmsmentioning
confidence: 99%
“…The present study mainly draws upon this small, but growing body of literature (e.g. Baker & Keogh 1995Leiminer & Baker 2000;MacLure & Walker 1999Silverman et al 1998). One of the main reasons for the paucity of descriptive research on the subject is the confidential and sensitive nature of PTMs (as underlined in Section 3.1).…”
Section: The Uncharted Territory Of Mediated Ptmsmentioning
confidence: 99%
“…Tidigare forskning om utvecklingssamtal visar att föräldrar och pedagoger anser att dessa samtal är värdefulla inslag för att upprätthålla och utveckla relationen mellan hem och förskola eller skola (Baker & Keogh, 1995;Leiminer & Baker, 2000;Markström, 2005Markström, , 2006Markström, , 2008Pillet-Shore, 2003;Sandberg & Vuorinen, 2008;Vuorinen, 2010). Utvecklingssamtal i förskolan har tidigare främst studerats med fokus på relationen och gränserna mellan privat och offentligt, och där ansvaret för barnet i hemmet och förskolan förhandlas (Alasuutari, 2009;Alasuutari & Karila, 2010;Markström, 2009).…”
Section: Utvecklingssamtal I Förskolanunclassified
“…Utvecklingssamtal kan förstås som ett verktyg för styrning och normalisering till ett idealt förskolebarn, men även i förhållande till föräldrar (Alasuutari & Karila, 2010;Markström, 2010Markström, , 2011bMarkström, , 2013Vallberg-Roth & Månsson, 2008). Detta har bland annat studerats genom att fokusera samtalens interaktionella struktur, hur barn och föräldrar positioneras och vad som anses som normalt i relation till den institutionella ordningen (Alasuutari & Markström, 2011;Leiminer & Baker, 2000;Markström, 2009Markström, , 2011bSilverman, Baker & Keogh, 1998). Pedagoger kategoriserar ofta barn och deras beteende som bra eller dåligt genom språkliga strategier med benämningar som kan kopplas till olika diskurser, och när det gäller de yngsta barnen, ofta i linje med utvecklingspsykologisk teori och terminologi.…”
Section: Utvecklingssamtal I Förskolanunclassified
“…Previous research has shown that parent-teacher conferences in educational settings are complex practices in which different interests are represented (Alasuutari 2009;Leiminer and Baker 2000;MacLure and Walker 2000;Markström 2006Markström , 2009Silverman et al 1998). The findings suggest that the parent-teacher conferences primarily focus on assessing and evaluating the individual child (Baker and Keogh 1995;Markström 2006Markström , 2009Pillet-Shore 2003;Silverman et al 1998) and teachers often categorise children and their behaviour as good or bad drawing on different discourses and linguistic strategies (c.f.…”
Section: Introductionmentioning
confidence: 99%